Determination of effective elastic constants of two phase composites - (:unkn) unknown (Taylor and Francis - Balkema, 2013)
The objective of the present study is to determine the mechanical properties of the composite materials formed in two types. The first includes small particles in a matrix while the second involves thin fibers. During calculations a fictitious, homogeneous, linear-elastic and isotropic single material which is named as effective material is considered. The base of the theoretical calculation depends on the equality of the strain energies of the composite and the effective material under the same state of stress. Considering hydrostatic tension and simple torsion, the Bulk modulus and the shear modulus of the effective material have been calculated as a function of the concentration ratio, and the elastic constants of the components. Some experiments are also achieved for comparison. The volume ratio of the matrix is much bigger compared to the particles or fibers. This means that the present study deals with experiments for the low concentration ratios. © 2013 Taylor & Francis Group, London, UK.